Biowaste-source-dependent synthetic pathways of redox functional groups within humic acids favoring pentachlorophenol dechlorination in composting process. (February 2020) - Zhao, Xinyu; Tan, Wenbing; Peng, Jingjing; Dang, Qiuling; Zhang, Hui; Xi, Beidou
Highlights: Aromatic systems are the electron-accepting moieties facilitating PCP dechlorination. Sugar-amine condensation is the forming way of redox groups in protein-rich composts. Polyphenol pathway mainly exists in lignocellulose- and lignin-rich composts. Seven groups of bacterial communities involved in synthetic and catabolic pathway. Abstract: Humic acids (HAs) can function as electron mediators for contaminants transformation in different environments. The humus respiration can facilitate pentachlorophenol (PCP) dechlorination during different biowastes composting. However, different characteristics of synthetic pathways of redox functional groups within HAs during different biowastes composting have never been characterized. Herein, we assessed the synthetic pathways of redox functional groups within HAs from protein-, lignocellulose-, and lignin-rich composts that facilitated the microbially reductive dechlorination of PCP, respectively. The results show that the aromatic systems are the major electron-accepting moieties of HAs and function as electron shuttles to facilitate the PCP dechlorination. Amino acid and reducing sugar are the major precursors for the synthesis of redox functional groups within HAs in protein-rich composts, and polyphenols and amino acids are discerned as the significant components to synthesize redox functional groups of HAs in lignocellulose- and lignin-rich composts. Seven groups of bacterial communities based on relationships among remarkable precursors, key bacterial communities, and redox functional groups within HAs are classified as participants in the precursors' catabolism and aromatic system' anabolism. Furthermore, the significant environmental factors on the synthetic pathways of redox functional groups within HAs in composting are confirmed by structural equation models. Conclusively, the regulating methods for promoting PCP dechlorination by HAs during different biowastes composting are proposed. Our results can help in understanding the distinct formative mechanisms of redox functional groups within HAs during different biowastes composting, providing insights into a classification-oriented approach for recycling utilization of different biowastes.